RESISTANCE TO OXAMNIQUINE OF A Schistosoma mansoni STRAIN ISOLATED FROM PATIENT SUBMITTED TO REPEATED TREATMENTS - M.Z. COELHO; F.C. LIMA E SILVA; J.A. NOGUEIRA-MACHADO (Revista do Instituto de Medicina Tropical de São Paulo, 1997)
A strain of Schistosoma mansoni (R1) was isolated from patient previously submitted to four treatments with oxamniquine, and to another one with praziquantel. The results obtained with chemotherapeutic test, by using oxamniquine in mice infected with the strains R1 and LE (standard), showed an evident resistance to the drug in worms of the strain R1. Thus, at the dose of 250 mg/kg oxamniquine, all mice (17) infected with the LE strain did not show surviving worms, whereas 12 out of 17 mice infected with the R1 strain presented surviving worms. At the dose of 200 mg/kg, the LE strain showed recovery rates of 1.06% and 20.58%, whereas the R1 strain presented 18.57% and 61.14%, for male and female worms, respectively. At the dose of 100 mg/kg, the recovery of male worms was 2.6% for the LE strain, and 29.9% for the R1 strain. At the same dose, the recovery of females did not show statistically significant differences between the two strains (LE = 76.38%, R1 = 79.12%). Praziquantel showed similar antischistosomal activity against both studied strains, when administered at the dose of 500 mg/kg Resistência ao oxamniquine de uma cepa de Schistosoma mansoni isolada de paciente submetido a repetidos tratamentos Uma cepa de Schistosoma mansoni (R1) foi isolada de paciente previamente submetido a quatro tratamentos com oxamniquine e a um outro com praziquantel. Os resultados obtidos com o teste quimioterapêutico, usando oxamniquine em camundongos infectados com as cepas R1 e LE (padrão) mostraram resistência evidente à droga em vermes de cepa R1. Assim, com a dose de 250 mg/kg de oxamniquine, todos os camundongos (17) dos 17 camundongos infectados com a cepa R1 apresentaram vermes sobreviventes. Com a dosagem de 200 mg/kg a cepa LE mostrou taxas de recuperação de 1,06 e 20,58% enquanto a cepa R1 apresentou 18,57 e 61,14% para os vermes machos e fêmeas, respectivamente. Com a dose de 100 mg/kg a recuperação de vermes machos foi de 2,6% para a Cepa LE e 29,9% para a R1. Com a mesma dosagem, a recuperação de fêmeas não ...